Language and Thought in Classical Arabic Poetry: A Linguistic–Philosophical Analysis - Asep Majidi Tamam; Adi Supardi; Rohanda; Dadan Mardani (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Salatiga, 2026)
This article examines the relationship between language and thought in classical Arabic poetry from a linguistic–philosophical perspective. Language is viewed not only as a medium of expression but also as a framework for shaping human thought and worldview. In classical Arabic literary tradition, poetry functions as an intellectual and cultural space where linguistic structures, rhetorical devices, and symbolic expressions reflect rational, emotional, and spiritual ways of thinking. This study employs a qualitative approach using textual analysis and literary hermeneutics to analyze selected classical Arabic poems, including pre-Islamic poetry, the works of al-Mutanabbī, and Sufi poetry represented by Ibn al-Fāriḍ. The analysis focuses on linguistic features such as metaphor (isti‘ārah), symbolism, rhythm, and rhyme, and their role in constructing cognitive and philosophical meanings. Drawing on theories of linguistic relativity and conceptual metaphor, this study argues that poetic language in classical Arabic literature not only represents thought but also shapes it. The findings show that classical Arabic poetry reflects symbolic and analogical thinking, where language connects rational reflection, emotional experience, and spiritual awareness. This study contributes to Arabic literary and linguistic studies by highlighting the cognitive and philosophical dimensions of poetic language in the classical Arabic tradition.